Sex-Dependent Variations in Gene Expression in Corneal Endothelial Cells among Healthy Individuals and Patients with Fuchs Endothelial Corneal Dystrophy - Nakagawa, Tatsuya; Tateishi, Ayana; Tokuda, Yuichi; Nakano, Masakazu; Tashiro, Kei; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Koizumi, Noriko (Cornea, 2025)
Purpose:Fuchs endothelial corneal dystrophy (FECD) displays a higher incidence in females than in males, yet the underlying mechanism remains unclear. This study aimed to elucidate sex-dependent differential gene expressions in corneal endothelial cells (CECs) from healthy non-FECD individuals and from patients with FECD.Methods:RNA-Seq data from CECs of non-FECD subjects (3 males, 4 females) and FECD subjects (5 males, 5 females) were analyzed to identify differentially expressed genes (DEGs) between the sexes. We used heatmaps and principal component analysis for expression pattern visualization and Gene Ontology analysis for functional categorization of DEGs.Results:Among the non-FECD subjects, we identified 341 DEGs - 143 upregulated and 198 downregulated - in females relative to males. For FECD subjects, 309 DEGs were discovered, with 215 upregulated and 94 downregulated in females compared with males. Heatmaps exhibited hierarchical clustering by sex, whereas principal component analysis delineated distinct male and female clusters in both non-FECD and FECD cohorts. Gene Ontology enrichment analysis linked the upregulated genes in non-FECD females to steroid hormone response, and downregulated ones to cyclin-dependent protein kinase activity. In females with FECD, upregulated genes were associated with immune responses and downregulated genes with peptide hormone binding.Conclusions:To our knowledge, these findings are the first to reveal distinct gene expression patterns in CECs between sexes. The observed variations suggest a potential genetic basis for the observed sex disparity in FECD prevalence. Further investigation is warranted to explore these associations and their implications for the pathogenesis of FECD.
CRIS-Team Scopus Importer:2025-01-31
Keywords: corneal endothelial cell; Fuchs endothelial corneal dystrophy; RNA sequencing; sex-biased gene